Development and validation of a questionnaire measuring secondary students' genetic essentialism and teleology (GET) conceptions. Issue 2 (22nd January 2020) - Stern, Florian; Kampourakis, Kostas; Delaval, Marine; Müller, Andreas
ABSTRACT: In this article, we describe the main phases in the development and validation of a questionnaire measuring secondary students' teleology and essentialism conceptions in the context of genetics. The validation process involved 714 Swiss and French secondary school students from 14 different schools. The process included interviews, several pilot studies, experts' feedback, and lasted from January 2017 to May 2018. The final version of the test consists of 20 items based on an ordinal scale, which measure teleology and essentialism conceptions in the context of genetics. Exploratory factor analysis showed a structure with three factors and Cronbach's alpha values indicated a good internal consistency of the items. We also report findings on students' genetic determinism conceptions, even though the respective items were not included in the final questionnaire because their psychometric properties were not as good as those for genetic teleology and genetic essentialism. Implications for science education are discussed.